Sindbis Virus Infection Causes Cell Death by nsP2-Induced Transcriptional Shutoff or by nsP3-Dependent Translational Shutoff - Akhrymuk, Ivan (J Virol, 2018)
Sindbis virus (SINV) is a representative member of the Alphavirus genus in the Togaviridae family. The hallmark of SINV replication in vertebrate cells is a rapid development of the cytopathic effect (CPE), which usually occurs within 24 h postinfection. Mechanistic understanding of CPE might lead to development of new prophylactic vaccines and therapeutic means against alphavirus infections. However, development of noncytopathic SINV variants and those of other Old World alphaviruses was always highly inefficient and usually resulted in selection of mutants demonstrating poor replication of the viral genome and transcription of subgenomic RNA. This likely caused a nonspecific negative effect on the rates of CPE development. The results of this study demonstrate that CPE induced by SINV and likely by other Old World alphaviruses is a multicomponent process, in which transcriptional and translational shutoffs are the key contributors. Inhibition of cellular transcription and translation is determined by SINV nsP2 and nsP3 proteins, respectively. Defined mutations in the nsP2-specific peptide between amino acids (aa) 674 and 688 prevent virus-induced degradation of the catalytic subunit of cellular-DNA-dependent RNA polymerase II and transcription inhibition and make SINV a strong type I interferon (IFN) inducer without affecting its replication rates. Mutations in the nsP3 macrodomain, which were demonstrated to inhibit its mono-ADP-ribosylhydrolase activity, downregulate the second component of CPE development, inhibition of cellular translation, and also have no effect on virus replication rates. Only the combination of nsP2- and nsP3-specific mutations in the SINV genome has a dramatic negative effect on the ability of virus to induce CPE. IMPORTANCE Alphaviruses are a group of important human and animal pathogens with worldwide distribution. Their characteristic feature is a highly cytopathic phenotype in cells of vertebrate origin. The molecular mechanism of CPE remains poorly understood. In this study, by using Sindbis virus (SINV) as a model of the Old World alphaviruses, we demonstrated that SINV-specific CPE is redundantly determined by viral nsP2 and nsP3 proteins. NsP2 induces the global transcriptional shutoff, and this nuclear function can be abolished by the mutations of the small, surface-exposed peptide in the nsP2 protease domain. NsP3, in turn, determines the development of translational shutoff, and this activity depends on nsP3 macrodomain-associated mono-ADP-ribosylhydrolase activity. A combination of defined mutations in nsP2 and nsP3, which abolish SINV-induced transcription and translation inhibition, in the same viral genome does not affect SINV replication rates but makes it noncytopathic and a potent inducer of type I interferon.